Second-harmonic generation microscopy of murine scleral remodeling by collagenase and reparative collagen mimetic peptides - Savage, Daniel E.; Tecse, Aldo; Zhou, Jiaxi; Germann, James A.; Buckley, Mark R.; Baratta, Robert O.; Del Buono, Brian J.; Schlumpf, Eric; Telias, Michael; Marcos, Susana (Frontiers in Medicine, 2025)
IntroductionMyopia, resulting from an excessive axial elongation of the eye, is increasing worldwide at alarming rates. This investigation is a pilot study to determine if a novel collagen mimetic peptide (CMP) has a reparative function for scleral collagen organization after collagenase digestion, a cause for scleral thinning and increased creep rates, as this may have application in the pharmacologic treatment of myopia.MethodsFresh, ex vivo, scleral tissue samples from 3 albino Sprague–Dawley rats (5 eyes) and from 8 C57/Black mice (8 eyes) underwent sequential collagenase digestion and treatment with a CMP solution. Full-thickness second-harmonic generation (SHG) microscopy was performed over a 200 μm × 200 μm area through depth on each of the untreated samples (either scleral tissue samples or full intact eyes), and again after each sequential treatment. The organization of the collagen fibers at each tissue depth was quantified using a previously validated order coefficient (OC). This measure of collagen organization was then used to compare between the untreated, collagenase-digested, and CMP-treated tissue.ResultsSHG microscopy of the untreated scleral tissue showed a high degree of organization. Collagenase treatment resulted in a subjective straightening of the collagen fibers and a widening of the inter-fiber spacing with a statistically significant reduction of the OC (p < 0.05). CMP treatment of digested sclera resulted in a collagen organization that was more similar (i.e., not significantly different) from untreated tissue at depths up to 60 μm (p < 0.05). The restoration of collagen organization was found both in the treated excised rat scleral samples (OC: 0.30 ± 0.01 normal tissue, 0.37 ± 0.05 collagenase-digested and 0.28 ± 0.03 CMP-treated until 20 μm) and on intact mice eyes (OC: 0.25 ± 0.01 normal tissue, 0.30 ± 0.05 collagenase-digested and 0.24 ± 0.01 CMP-treated).DiscussionCMP treatment induced scleral collagen reorganization after collagenase digestion in murine models. These effects are consistent with inhibition or reversal of collagen enzymatic digestion. These results suggest that specific CMPs may have utility in the treatment of progressive myopia.